Perancangan Prototipe Dashboard untuk Analisis Pelayanan Nasabah dan Strategi Digital Marketing pada Agen BRILink Cuan Komunika - Rosmini Rosmini; Tedi Budiman Budiman (INTERNAL (Information System Journal), 2025)
The rapid development of digital technology has transformed how BRILink agents provide services and implement marketing strategies. This study designs a dashboard prototype to evaluate customer service performance, including transfer and cash withdrawal transactions, and to support data-driven decision-making. The research applies a design-based methodology, with data collected through surveys, interviews, and user needs analysis. The dashboard prototype, developed using Figma, presents service indicators, transaction metrics, and digital marketing performance in real-time through interactive visualizations. The evaluation results indicate that the dashboard facilitates monitoring service quality and supports more accurate digital marketing strategic planning. This research contributes to the development of digital tools aimed at enhancing service performance and marketing effectiveness for BRILink agents by integrating key metrics such as Conversion Rate, Customer Satisfaction Index (CSI), and Average Transaction Value (ATV).